1995
DOI: 10.1111/j.1471-0528.1995.tb10878.x
|View full text |Cite
|
Sign up to set email alerts
|

Scalp blood lactate: a new test strip method for monitoring fetal wellbeing in labour

Abstract: Objective To determine fetal scalp blood lactate with a new test strip method in parturients with normal and abnormal cardiotocograms during labour and to describe the relation to maternal lactate, fetal scalp blood pH, cord artery lactate and acid‐base balance. Setting Labour wards at the University Hospitals of Huddinge and Lund and at the County Hospital of Östersund, Sweden. Materials and method Fetal scalp blood was sampled for lactate (n= 269) and pH (n= 285) determination in 177 partur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 19 publications
1
43
0
2
Order By: Relevance
“…Furthermore, the value of scalp lactate has been found to be identical to scalp pH in the prediction of Apgar scores [7] . In a prospective randomized trial, Westgren et al [11] showed that scalp lactate sampling was more easily feasible than scalp pH, especially with the advent of cheap handheld lactate meters [7,8] .…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Furthermore, the value of scalp lactate has been found to be identical to scalp pH in the prediction of Apgar scores [7] . In a prospective randomized trial, Westgren et al [11] showed that scalp lactate sampling was more easily feasible than scalp pH, especially with the advent of cheap handheld lactate meters [7,8] .…”
Section: Introductionmentioning
confidence: 91%
“…There is a rise in lactate concentration in cases of fetal metabolic acidosis, due to hypoxia and anaerobic metabolism [6] . Indeed, strong correlations exist between lactate concentration, BD and pH in the umbilical cord blood [7][8][9] , and between scalp lactate and umbilical cord lactate [10] . Furthermore, the value of scalp lactate has been found to be identical to scalp pH in the prediction of Apgar scores [7] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in fetal monkeys showed a good correlation of acid-base parameters between scalp and carotid blood [6], and human data have shown similar correlations between pH and lactate values obtained in scalp blood and those recorded shortly after birth in the umbilical artery and vein [7][8][9][10][11]. However, correlation of these values with newborn outcome depends on the time interval between scalp sampling and birth [12].…”
Section: Fetal Blood Sampling For Ph and Lactate Measurementsmentioning
confidence: 99%
“…Furthermore, in cases of acidemia, it is maintained that far more time than foreseen is spent from decision to perform a FBS to when the infant is delivered [2,9] . The introduction of lactate analysis in scalp blood has, however, simplifi ed the method, since only 5 µ L of blood is required for lactate determination [64] . Interpretation value for normal lactate is ( < 4.2 mmol/L), pre-acidocis (4.2 -4.8 mmol/L) and acidosis ( > 4.8 mmol/L) [62,84] .…”
Section: Fetal Blood Sampling (Fbs)mentioning
confidence: 99%